Plasma Circulating Tumor Epstein–Barr Virus for the Surveillance of Cancer Progression in Bone-Only Metastatic Nasopharyngeal Carcinoma - Liu, Guo-Ying; Xia, Wei-Xiong; Bi, Zhuo-Fei; Lu, Nian; Li, Wang-Zhong; Bei, Wei-Xin; Liang, Hu; Xie, Jun-Zhi; Liu, Yi-Min; Yao, He-Rui; Xiang, Yan-Qun (Frontiers in Oncology, 2022)
Background Plasma Epstein–Barr virus DNA (EBV-DNA) is a sensitive and specific biomarker for nasopharyngeal carcinoma (NPC). We investigated whether longitudinal monitoring of EBV-DNA could accurately detect clinical disease progression in NPC patients with bone-only metastases. Methods In this retrospective study, a total of 105 patients with bone-only metastatic NPC who were treated with platinum-based first-line chemotherapy were enrolled. Undetectable EBV-DNA after first-line chemotherapy was defined as a biochemical complete response (BCR). The correlation of the EBV-DNA dynamic status with overall survival (OS) and progression-free survival (PFS) was determined by Cox regression. The correlation between non-normalized EBV-DNA period and PFS period was determined. Results After a median follow-up time of 53.4 months [Interquartile range (IQR): 42.8–80.6], 64 patients had disease progression. Thirty-nine of 105 patients (37.1%) had a BCR at all follow-up time points, and none of these 39 patients had disease progression, corresponding to a negative predictive value (NPV) of 100%. Sixty-six patients had a detectable EBV-DNA during surveillance, with 64 diagnosed as disease progression at the last follow-up, for a positive predictive value (PPV) of 97.0%. Actuarial 3-year OS rates were 45.0% for patients with detectable EBV-DNA during posttreatment surveillance and 100% for patients with undetectable EBV-DNA. Lastly, median lead time between non-normalized EBV-DNA and clinically proven progression was 5.87 ± 0.67 months. Conclusions Taken together, EBV-DNA provided predictive value for the bone-only metastatic NPC patients. The results should be validated in prospective randomized studies.